SUBJECTIVE COGNITIVE COMPLAINTS IN A PATIENT WITH KERATOCONUS: COGNITIVE IMPAIRMENT OR - Ara G. Kaprelyan; Alexandra J. Tzoukeva; Ivan N. Dimitrov; Borislav Ivanov; Nadejda S. Deleva (Peytchinski Publishing, 2012)
Keratoconus is a disorder affecting the cornea, characterized by its variably progressive central thinning, which results in conically shaped protrusion. Patients with keratoconus are sometimes described as having peculiar personality characteristics. We present the case of a patient with keratoconus, complaining of impairment of concentration and memory disturbances. He reported slow progression of the complaints but was fully capable of performing his professional and social activities. Neuropsychological assessment confirmed fluctuations of active attention and diminished concentration. Long term memory was within normal limits, but closer to the lower level). MMSE score was 27. No significant changes were observed one year after baseline assessment. No major psychiatric disorder was found. In this clinical case we are tempted to discuss the possible role of keratoconus, which, as it has been described in the literature, could lead to some slight changes of behavior, forming a "keratoconic personality".